Effects of Different Chromium Compounds on Hematology and Inflammatory Cytokines in Rats Fed High-Fat Diet - Dworzański, Wojciech; Sembratowicz, Iwona; Cholewińska, Ewelina; Tutaj, Krzysztof; Fotschki, Bartosz; Juśkiewicz, Jerzy; Ognik, Katarzyna (Frontiers in Immunology, 2021)
The aim of the study was to determine how a high-fat diet supplemented with various forms of chromium affects haematological and immune parameters of the blood of rats. The rats received a standard diet or a high-fat diet supplemented with chromium at 0.3 mg/kg body weight (BW) in the form of chromium(III) picolinate, chromium(III)-methionine or nano-sized chromium. Selected haematological parameters were determined in the blood of the rats, including total white blood cell (WBC) count, leukogram, red blood cell (RBC) count, haemoglobin level (HGB), haematocrit (HCT), platelet count (PLT) and platelet percentage (PCT), as well as immune parameters: levels of immunoglobulins A and E (IgA and IgE), interleukin-6 (IL-6), interleukin-2 (IL-2), and tumour necrosis factor α (TNF-α); activity of ceruloplasmin (Cp); and levels of caspase 3 and 8 (Casp3 and Casp8). Feeding rats a high-fat diet increased blood markers of induction of inflammation, ie pro-inflammatory cytokines IL-6 and TNF-α, and also significantly increased IgE. The diet had no effect on the blood count, except for an increase in the number of granulocytes and their percentage in the leukogram. The chromium compounds tested, particularly Cr-Met and Cr-NPs, stimulated the immune system of the rats, as indicated by increased concentrations of IgA, IgE, IL-2, IL-6, TNF-α and Cp. Given the increase in inflammatory mediators induced by chromium, its use to mitigate the effects of a high-fat diet should not be recommended. Moreover, chromium picolinate and chromium nanoparticles were shown to increase the content of caspase 3 and 8 in the blood of rats, which indicates a pro-apoptotic effect. The unfavourable effects of the use of chromium nanoparticles include reductions in the WBC count and the thrombocyte count (leuko- and thrombopaenia).